Some psychosocial variables associated with the poor academic performance from the first year students of the medicine career - Ángel García Gascón; Annia Yolanda Del Toro Añel; Elio Cisneros Prego; Odalis Querts Méndez; Xiomara Cascaret Soto (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive and cross-sectional study of 236 students who did not pass the test in the matter Morphophysiolgy III in the first year of Medicine career was carried out. They belonged to the Medical Sciences Faculty 2 in Santiago de Cuba, from January to May, 2016, with the purpose of determining some psychosocial aspects associated with the poor performance of these students. A survey, Holmes and Rahe stress scale, the anxiety feature-state and Beck depression stockchecks were carried out. The frequent and partial evaluation marks, the theoretical and practical integrating final exam as well as the experience of the student in the matter were taken into account. In the series there was a prevalence of inadequate life styles, divorce, lack of motivation and high levels of stress.